Genome-wide Analysis and Expression Profiling Suggest Diverse Roles of TCP Genes During Development and Stress Responses in Grapevine (Vitis vinifera L) - Min, Z.; Zhang, Y.; Li, R.; Liu, M.; Ju, Y.; Fang, Y.; Meng, J. (South African Journal of Enology and Viticulture, 2018)
Teosinte branched 1/cycloidea/proliferating cell factor 1 (TCP) proteins are plant-specific transcription factors playing crucial roles in various biological processes, such as leaf development, flower symmetry, shoot branching and senescence. However, no comprehensive analysis of the TCP gene family has been reported in grapevine (Vitis vinifera L). Herein, a total of 15 TCP family members were identified in the genome of grapevine, located on eight of the 19 chromosomes. Phylogenetic and structural analyses showed that the VvTCPs were classified into two groups, designated as Class I and Class II. The Class II genes were further divided into two subclasses, the CIN subclass and the CYC/TB1 subclass. Genes belonging to the same subclass shared similar gene structures, conserved domains and motifs. Real-time PCR showed that almost all members of Class II exhibited organ-specific expression patterns, while members of Class I and the CIN Class were ubiquitously expressed in all the tissues examined, indicating multiple roles in the development of different grapevine organs. In addition, many members were strongly modulated by abiotic (cold, heat, drought) and biotic (downy mildew and powdery mildew infection) stresses, suggesting important and diverse regulatory roles in adverse conditions and plant immunity. The comprehensive in silico analysis of the grapevine TCP transcription factor family gives us some references to potential functions in grapevine development and stress responses.